Artificial Intelligence and Media Integrity in Digital Media: A Literature Review on Algorithmic Disinformation and Communication Ethics - Riesta Ayu Oktarina; Rahmad Gatut Marwanto; E. Rizky Wulandari; Edelweis Putri Prima (LPPM Stikosa - AWS, 2025)
The development of artificial intelligence (AI) has fundamentally transformed the digital media ecosystem, particularly in the processes of information production, distribution, and legitimation. While AI enables efficiency and content personalization, it simultaneously raises critical challenges to media integrity and communication ethics. This article aims to critically examine the role of artificial intelligence in shaping the crisis of digital media integrity, with particular attention to algorithmic disinformation, biased information distribution, and the ethical implications of AI-based media practices. This study employs a qualitative approach through a literature review of ten international scholarly journals published between 2015 and 2025. The findings indicate that AI functions as a structural actor within the digital media ecosystem by reinforcing the logic of the attention economy, accelerating the spread of disinformation, and reshaping journalistic ethical standards. At the same time, AI also presents potential as a tool for disinformation mitigation when supported by ethical frameworks, algorithmic transparency, and effective governance. This article concludes that digital media integrity in the age of artificial intelligence constitutes a systemic issue that requires a multidimensional approach integrating communication ethics, technology regulation, and platform accountability.